1990
DOI: 10.1016/s0886-3350(13)80708-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of posterior capsular opacification Part II: Histopathological and in vitro culture findings

Abstract: The most interesting sources of information about the pathogenesis of posterior capsular opacification seem to be histopathological studies and in vitro tissue cultures. Since our surgical technique is extracapsular cataract extraction, the explants we used for tissue culture consisted of the anterior capsule epithelial sheet without the equatorial germinative zone. We successfully overcame several problems by using the autologous plasma clot culture method. This medium, considered the optimal one for this typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…It is accepted that posterior migration of lens epithelium is one histological feature of cataract formation. On in vitro culture of lens epithelial cells, Frezotti et al [12] found two principal forms of evolution of these cells, i.e. fibrosis (pseudometaplasia) and multiple pearl-like formation (Elschnig cells).…”
Section: Discussionmentioning
confidence: 99%
“…It is accepted that posterior migration of lens epithelium is one histological feature of cataract formation. On in vitro culture of lens epithelial cells, Frezotti et al [12] found two principal forms of evolution of these cells, i.e. fibrosis (pseudometaplasia) and multiple pearl-like formation (Elschnig cells).…”
Section: Discussionmentioning
confidence: 99%
“…SMA, a specific marker for myofibroblastic cells, has been previously shown to accumulate in cultured LEC exposed to certain growth factors [12,17], anterior subcapsular cataracts [32], and PCO [9,18]. Importantly, LEC producing SMA are thought to be responsible for the localized capsular wrinkling associated with PCO and which is often associated with light scatter.…”
Section: Discussionmentioning
confidence: 99%
“…Most oculists believe that remaining LECs are able to proliferate and migrate to form a monolayer, or multilayers of cells over the anterior surface of the posterior capsule. It is believed that the cells in this membrane undergo phenotypic change to fibroblast-like cells, whose contraction causes extensive wrinkling of the posterior capsule [11][12][13] and which, in addition, secrete extracellular matrix [14,15].…”
Section: Discussionmentioning
confidence: 99%